2019
DOI: 10.17159/2411-9717/17/380/2019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hot deformation behaviour of Nb-Ti microalloyed high-strength steel

Abstract: The hot deformation behaviour of Nb-Ti microalloyed high-strength steel was investigated. Hot compression tests were conducted in the temperature range 900 to 1100°C under strain rates of 0.1, 1, and 5 s-1. Dynamic recrystallization (DRX) occurs as the main flow softening mechanism at high temperature and low strain rate. The hot deformation activation energy was calculated to be about 404 699 J/mol. The constitutive equation was developed to describe the relationship between peak stress, strain rate, and defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…31,32) It has been demonstrated that Nb has a strong detrimental effect when its content ranges between 0,03-0,04 wt.%Nb, which could promote cracking due to carbo-nitrides precipitation associated with low ductility. 22,28,[33][34][35][36] Yet, Nb is still used due to its beneficial effects on final mechanical properties. A possible way to circumvent this issue is to combine Nb with V and Ti which have a lesser effect on ductility loss.…”
Section: Identification Of Cracking Issues and Process Improvements Tmentioning
confidence: 99%
“…31,32) It has been demonstrated that Nb has a strong detrimental effect when its content ranges between 0,03-0,04 wt.%Nb, which could promote cracking due to carbo-nitrides precipitation associated with low ductility. 22,28,[33][34][35][36] Yet, Nb is still used due to its beneficial effects on final mechanical properties. A possible way to circumvent this issue is to combine Nb with V and Ti which have a lesser effect on ductility loss.…”
Section: Identification Of Cracking Issues and Process Improvements Tmentioning
confidence: 99%
“…Plenty of work has been carried out to study the influences of process parameter and microstructure evolution on flow-stress evolution of various steels. The effects of strain rate, strain, and temperature on flow-stress were considered, and the flow-stress models of Nb-Ti steel [1] and 5CrNiMoV steel [2] for single-pass compression were constructed based on the Arrhenius model. To reflect the influence of dislocation, segmented flow-stress models of AZ61 magnesium alloy [3] and 34CrNiMo6 steel [4] were established based on the Kocks-Mecking model during hot compression.…”
Section: Introductionmentioning
confidence: 99%
“…
In this work, multi-pass compressions were performed at various strain rates (0.01 s −1 , 0.1 s −1 , 1 s −1 , 10 s −1 ), temperatures (950 • C, 1050 • C, 1150 • C), inter-pass holding time (1 s, 10 s, 30 s, 120 s, 600 s), interrupt strains (0.3, 0.4, 0.5, 0.6), and total pass numbers (1,2,3,4). The intriguing finding was that the recrystallized fraction, average dislocation density, and plastic cumulative strain were partly eliminated during inter-pass holding, resulting in the early occurrence of recrystallization in subsequent compression.
…”
mentioning
confidence: 99%